Physical Function, Hyperuricemia, and Gout in Older Adults. Issue 12 (December 2015) - Burke, Bridget Teevan; Köttgen, Anna; Law, Andrew; Gwen Windham, Beverly; Segev, Dorry; Baer, Alan N.; Coresh, Josef; McAdams‐DeMarco, Mara A.
Abstract : Objective: Gout prevalence is high in older adults and those affected are at risk of physical disability, yet it is unclear whether they have worse physical function. Methods: We studied gout, hyperuricemia, and physical function in 5, 819 older adults (age ≥65 years) attending the 2011–2013 Atherosclerosis Risk in Communities Study visit, a prospective US population‐based cohort. Differences in lower extremity function (Short Physical Performance Battery [SPPB] and 4‐meter walking speed) and upper extremity function (grip strength) by gout status and by hyperuricemia prevalence were estimated in adjusted ordinal logistic regression (SPPB) and linear regression (walking speed and grip strength) models. Lower scores or times signify worse function. The prevalence of poor physical performance (first quartile) by gout and hyperuricemia was estimated using adjusted modified Poisson regression. Results: Ten percent of participants reported a history of gout and 21% had hyperuricemia. There was no difference in grip strength by history of gout ( P  = 0.77). Participants with gout performed worse on the SPPB test; they had 0.77 times (95% confidence interval [95% CI] 0.65, 0.90, P  = 0.001) the prevalence odds of a 1‐unit increase in SPPB score and were 1.18 times (95% CI 1.07, 1.32, P  = 0.002) more likely to have poor SPPB performance. Participants with a history of gout had slower walking speed (mean difference −0.03; 95% CI −0.05, −0.01, P < 0.001) and were 1.19 times (95% CI 1.06, 1.34, P  = 0.003) more likely to have poor walking speed. Similarly, SPPB score and walking speed, but not grip strength, were worse in participants with hyperuricemia. Conclusion: Older adults with gout and hyperuricemia are more likely to have worse lower extremity, but not upper extremity, function.